A new method for designing piezo transducers with connected two-phase electrode. (15th January 2023) - Donoso, A.; Aranda, E.; Ruiz, D.
Highlights: A new method for designing transducers with connected electrodes is developed. Optimized electrode configurations just require two wires, one for each phase. The method can be used regardless of the objective function and constraints involved. Piezo transducers obtained are functional devices of easier manufacturability. The method is valid to impose connectivity over two phases in other contexts. Abstract: In this paper, we present a new method for designing piezoelectric transducers with connected two-phase electrode. The electrode design problem is formulated as an optimization problem, and the most significant contribution is modeling of connectivity constraints by using results from graph theory. Several examples are shown to corroborate that optimized electrode configurations lead to devices of easier manufacturability, still bearing in mind functionality.